2021
DOI: 10.3390/ijerph18179340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dry-Land Training Programs on Swimming Turn Performance: A Systematic Review

Abstract: Swimming coaches have prescribed dry-land training programs over the years to improve the overall swimming performance (starts, clean swimming, turns and finish). The main aim of the present systematic review was to examine the effects of dry-land strength and conditioning programs on swimming turns. Four online databases were scrutinised, data were extracted using the Preferred PRISMA guidelines and the PEDro scale was applied. A total of 1259 articles were retrieved from database searches. From the 19 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The researchers attribute this to the fact that the physical therapy used and the flexibility and strength exercises that were used rehabilitated the working muscles of Monofin. which agrees with (Fone & van den Tillaar, 2022;Hermosilla et al, 2021;Karpiński et al, 2020) In that the regular physiotherapy based on scientific foundations is a quick and inexpensive solution to recover from injuries and ensure that the injury does not develop and get rid of pain, and its effect is more noticeable more quickly on large muscles .…”
Section: Discussionsupporting
confidence: 76%
“…The researchers attribute this to the fact that the physical therapy used and the flexibility and strength exercises that were used rehabilitated the working muscles of Monofin. which agrees with (Fone & van den Tillaar, 2022;Hermosilla et al, 2021;Karpiński et al, 2020) In that the regular physiotherapy based on scientific foundations is a quick and inexpensive solution to recover from injuries and ensure that the injury does not develop and get rid of pain, and its effect is more noticeable more quickly on large muscles .…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, it has been shown that high levels of maximum strength in various exercises (e.g., bench press, pull-up, back squat, horizontal rows, etc.) correlate with many technical components of a swimming race, such as trunk stability during the stroke, gliding phase, diving phase, turning phase, stroke length, stroke frequency, and stroke index [ 2 , 3 , 4 , 6 , 7 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], ultimately translating into optimized swimming velocity [ 19 ]. Nonetheless, vertical pulling gestures are the most used and effective motions for evaluating force–velocity production in swimming performances [ 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have been performed to solve controversy by systematically aggregating the literature related to strength and conditioning practices in WSA [ 52 , 53 , 67 , 68 ]. However, most of these reviews did not consider including a meta-analysis, or addressed a restricted population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This leaves the question of the effects of single-mode PJT unanswered. Furthermore, when PJT studies were included, the number was low ( n = 6 studies [ 53 ]; n = 4 studies [ 52 ]; n = 2 studies [ 68 ]). To account for the previous limitations (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation